Penerapan Model Pembelajaran Kombinasi PBL dan Kooperatif Tipe TGT untuk Meningkatkan Aktivitas Belajar dan Hasil Belajar Ekonomi Siswa - I Kadek Nik Agus Suarnata; Made Ary Meitriana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
Learning activity and learning outcomes are important indicators of successful economics learning. Previous studies have demonstrated that the Problem Based Learning (PBL) model and the Teams Games Tournament (TGT) cooperative learning model are effective in improving learning quality. However, studies integrating these two models to enhance students' learning activity and learning outcomes in economics through classroom action research remain limited. Therefore, this study aimed to determine: (1) the improvement of students’ learning activity, (2) the improvement of students’ learning outcomes, and (3) students’ responses after the implementation of the combined PBL and TGT learning models in Class XA of SMA Negeri 1 Sawan. This study employed Classroom Action Research (CAR), conducted in two cycles involving 34 students of Class XA at SMA Negeri 1 Sawan. Data were collected through observation, achievement tests, and questionnaires, and were analyzed using descriptive quantitative techniques. The results showed that students’ learning activity increased from 72.08 in Cycle I to 88.66 in Cycle II. Learning mastery also improved from 58.82% in Cycle I to 82.35% in Cycle II, while students’ responses toward the learning implementation were categorized as highly positive, with an average score of 81.76. In conclusion, the integration of the PBL and TGT learning models effectively improved students’ learning activity and learning outcomes and can serve as an alternative instructional strategy to promote more active, collaborative, and student-centered economics learning.